IMPLEMENTASI INTERIOR NARATIF DALAM UPAYA MEMBANGUN NARASI ETNISITAS PADA MUSEUM NEGERI PROVINSI SUMATRA UTARA - Minadiah Purba; Gregorius Prasetyo Adhitama (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
Spanning eight ethnic cultures with different histories, the Province of North Sumatra keeps an abundance of historical stories, so it is significant to be able to build the narrative of ethnicity in the museum. The existence of the exhibition space that is still in the concept of a traditional museum makes the narrative in the cultural exhibition space in the museum has not yet developed. Narratives can build communication in creating understanding between humans and collections with story ideas conveyed. So that the narrative spatial approach is considered ideal to build a story. The purpose of this research is to be able to apply the interior of the narrative space through the context, content, scenarios, messages, and experiences of visitors. The method used in this study is a qualitative method summarized by the Design Thinking approach. The research data were obtained from literature studies, interviews, and direct observation of the exhibition room of the State Museum of North Sumatra. The result of this research is to create a maximum narrative in the exhibition space that will not be separated from the determination of Plot and Pace, arranged of Dramatic Arc, and the application of its presentation. The composition of the ethnic plot is divided into several life-to-death phases. Then determine the storyline includes a beginning, a muddle, and an end. And the last is the application of narrative elements, both the concept of content presentation to the setting of narrative media. So, by applying the narrative space approach in the North Sumatra State Museum, the presentation of ethnic narratives is more optimal and creates a different experience by playing with the emotions of visitors in each exhibition scenario.